Mu-opioid receptor binding measured by [ 11C]carfentanil positron emission tomography is related to craving and mood in alcohol dependence - Bencherif, Badreddine; Wand, Gary S; McCaul, Mary E; Kim, Yu Kyeong; Ilgin, Nese; Dannals, Robert F; Frost, James J (Biological psychiatry (1969), 2004)
The endogenous opioid system has been linked to alcohol dependence through animal and human studies. We investigated the relationship between alcohol craving and brain mu opioid receptors (μ-OR) in alcohol-dependent subjects. Regional brain μ-OR binding potential (BP) was measured using [ 11C]carfentanil positron emission tomography in eight male alcohol-dependent subjects undergoing alcohol withdrawal and eight matched control subjects. Self-reported alcohol craving, withdrawal, and mood were measured. Lower μ-OR BP was associated with higher craving in the right dorsal lateral prefrontal cortex, the right anterior frontal cortex, and right parietal cortex. In these regions, alcoholics showed lower mean μ-OR BP compared with control subjects. Mu-OR BP in four other brain regions also correlated with craving, but there were no group differences in receptor binding potential. Mu-OR BP also correlated with depressive symptoms in five brain regions, three of which were identified in the craving analyses. Results show a strong functional relationship between alcohol craving, mood, and μ-OR binding in specific brain regions of recently abstinent, alcohol-dependent men.